Analysis of Soybean Consumption in Indonesia - Istis Baroh; Livia Windiana; Ika Setya Ariyanti (Universitas Muhammadiyah Malang, 2022)
Soybean is one of the main food commodities after rice and corn. Indonesian people indicate that soy consumption will continue to increase yearly along with population, per capita income, and public awareness of food nutrition. Increased demand for soybeans can be linked to an increase in public consumption. The objectives of this study were 1) to analyze the development of soybean consumption in Indonesia and 2) to analyze the factors that influence soybean consumption in Indonesia. This type of research is descriptive with a quantitative approach. The type of data used is secondary data (time series). The analysis method used in this research is Trend Analysis with Moving Average and Multiple Linear Regression Analysis. The variables used are soybean price (X1), substitution price (peanuts) (X2), income per capita (X3), and soybean consumption (Y). The study's results using the trend test showed that the value forecast of soybean consumption for the next or future period was 0.29, where the MAD value was 0.01, the MSE value was 0, and the MAPE value was 0.04. The multiple linear regression test showed that the price of soybeans and income per capita had a significant effect on soybean consumption. In contrast, the substitution price had no significant effect on soybean consumption.